2015
DOI: 10.1111/epi.12937
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of screening for HLAA*31:01 prior to initiation of carbamazepine in epilepsy

Abstract: SUMMARYObjective: Carbamazepine causes severe cutaneous adverse drug reactions that may be predicted by the presence of the HLA-A*31:01 allele in northern European populations. There is uncertainty as to whether routine testing of patients with epilepsy is cost-effective. We conducted an economic evaluation of HLA-A*31:01 testing from the perspective of the National Health Service (NHS) in the United Kingdom. Methods: A short-term, decision analytic model was developed to estimate the outcomes and costs associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…HLA-A*31:01 has been associated with increased risk of carbamazepine-induced hypersensitivity reactions, ranging from maculopapular exanthema to severe blistering reactions, among subjects of European ancestry and in the Japanese population [172] , [173] . Recent economic modelling suggested that routine testing for HLA-A*31:01 in order to reduce the incidence of cutaneous adverse drug reactions in patients being prescribed carbamazepine for epilepsy is likely to represent a cost-effective use of health care resources [174] .…”
Section: Established Evidencementioning
confidence: 99%
“…HLA-A*31:01 has been associated with increased risk of carbamazepine-induced hypersensitivity reactions, ranging from maculopapular exanthema to severe blistering reactions, among subjects of European ancestry and in the Japanese population [172] , [173] . Recent economic modelling suggested that routine testing for HLA-A*31:01 in order to reduce the incidence of cutaneous adverse drug reactions in patients being prescribed carbamazepine for epilepsy is likely to represent a cost-effective use of health care resources [174] .…”
Section: Established Evidencementioning
confidence: 99%
“…This method allowed for the first time deep insight in the mechanism that triggers the T cell responses following CBZ application. Understanding the pathogenesis of life-threatening CBZ hypersensitivity in HLA-B∗15:02 carriers would support medication safety and cost-effective personalized treatment [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cost-effectiveness of pharmacogenetics testing in the treatment of epilepsy was evaluated in three studies. The latest study from Plumpton et al [ 50 ] focused on the HLA*A*31:01 allele screening test. An ICER of £37,314 (US$53,674) per cutaneous avoided ADR for a prior HLA*A*31:01 allele test and carbamazepine (CBZ) administration following the test result was calculated.…”
Section: Resultsmentioning
confidence: 99%